The Strange Career of the Convict Clause: US Prison Imperialism in the Panamá Canal Zone. (2019) - Weber, Benjamin D.
Abstract: This article follows the "convict clause" in the Thirteenth Amendment to the US Constitution – the exception for slavery and involuntary servitude to continue as punishment for crime – to the Panamá Canal Zone. It argues that US officials used the prison system not only to extract labor, but to structure racial hierarchy and justify expansionist claims to jurisdiction and sovereignty. It reveals how despite the purported "usefulness" of the Black bodies conscripted in this brutal labor regime, the prison system's operational modality was racial and gendered violence which exceeded the registers of political economy, penology, and state-building in which that usefulness was framed. The Canal Zone convict road building scheme then became a cornerstone from which Good Roads Movement boosters, who claimed the convict was a slave of the state, could push for the Pan-American Highway across the hemisphere. Afro-Panamanian and Caribbean workers, who were the majority of those forced into Canal Zone chain gangs, protested the racism and imperialism of the prison system by blending anti-colonial and anti-racist strategies and deploying a positive notion of blackness as solidarity and race pride. Their efforts and insight offer an understanding of the US carceral state's imperial dimensions as well as enduring lessons for movements struggling to broaden the meaning and experience of freedom in the face of slavery's recurrent afterlives.